2017
DOI: 10.1111/disa.12225
|View full text |Cite
|
Sign up to set email alerts
|

The Student Volunteer Army: a ‘repeat emergent’ emergency response organisation

Abstract: This paper seeks to contribute to understanding of the factors associated with an effective emergent emergency response organisation and to provide new insights into this understudied area. It examines, through an analysis of a range of textual resources, the emergence and re-emergence of the Student Volunteer Army (SVA) during the devastating earthquakes in Canterbury, New Zealand, in 2010-11. This evaluation is conducted in relation to the four key features of an effective emergency response organisation: ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 24 publications
1
21
0
Order By: Relevance
“…Wildfires occurred repeatedly, albeit unpredictably, providing RFPAs and their BLM partners with the opportunity to develop and evolve their capacities. This is somewhat similar to the experience of ‘repeat emergent’ organisations in New Zealand (Carlton and Mills, ), but moved beyond what could be understood as repeat emergence. Trainings and time spent together in the off‐season appeared to help foster better relationships, mutual understanding, and increased skills.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Wildfires occurred repeatedly, albeit unpredictably, providing RFPAs and their BLM partners with the opportunity to develop and evolve their capacities. This is somewhat similar to the experience of ‘repeat emergent’ organisations in New Zealand (Carlton and Mills, ), but moved beyond what could be understood as repeat emergence. Trainings and time spent together in the off‐season appeared to help foster better relationships, mutual understanding, and increased skills.…”
Section: Discussionsupporting
confidence: 64%
“…Some of this work also challenges original conceptions of emergence as entirely non‐routine in all aspects. Recent research on ‘repeat emergent’ organisations in response to an earthquake and aftershocks in New Zealand identified groups that drew on prior experience and structures (Carlton and Mills, ). A study of the response to a major ice storm in Canada in January 1998 found that emergent groups developed from within the established response structure and did not conflict with it (Scanlon, ).…”
Section: Established and Expanding Disaster Response Organisationsmentioning
confidence: 99%
“…A long‐standing tradition in crisis and disaster studies has emphasized that convergence of citizen volunteers plays a major role on disaster sites (Drabek & McEntire, ; Dynes, ; Dynes & Quarantelli, ; Helsloot & Ruitenberg, ). Recent studies continue to show how response organizations, such as police, fire departments, and medical services relate to activities of these volunteers in crisis and disaster relief (Albris, In press Carlton & Mills, ; Lorenz, Schulze, & Voss, In press; Strandh & Eklund, In press). The potential of citizen involvement is tremendous, evidenced in literature through examples of citizens who converge on disaster sites to assist in damage assessment, shelter provisioning, search and rescue operations, and providing more general support to professional responders (Kendra & Wachtendorf, ; Solnit, ; Voorhees, ).…”
Section: Introductionmentioning
confidence: 99%
“…University/college students’ leadership in disaster settings has been briefly discussed. Carlton and Mills ( 2017 ) discovered that, after the Canterbury Earthquakes in New Zealand (2010−2011), the non-hierarchical organizational structure of community-based, non-profit disaster response agencies stimulated the leadership of their members, namely university student volunteers, to utilize their strengths and judgement in providing timely emergency assistance. However, most case studies relating to university/college students’ leadership have not elaborated on the influence of the gender factor.…”
Section: Female University/college Students and Disaster-specific Leadershipmentioning
confidence: 99%